PARE0016 Keep calm and tell me your story!: a narrative medicine pilot project for italian young people living with rheumatic and musculoskeletal diseases. (15th June 2017) - Viora, UG; Ostuzzi, S; ,
Abstract : Background: The 7th point of EULAR Young PARE's Youth Strategy states that "By 2020, every European country has an active national youth group for young people with rheumatic and musculoskeletal diseases (RMDs)". On this basis, ANMAR – Italian national association for people with RMDs – has engaged in the creation of a youth group dedicated to Italian young people (aged 18–35) living with RMDs: ANMAR Young was born in 2015, through EULAR's Knowledge Transfer Programme. During its first year of activities, ANMAR Young has launched the pilot project of a narrative medicine campaign called Keep Calm and Tell Me Your Story! Objectives: Keep Calm and Tell Me Your Story! was designed to make sure that the voice of young Italian people living with RMDs is heard, spread, and listened to. In its pilot phase, the project aimed to consult, engage, involve young rheumatic patients while building an Italian network. A major pilot phase's objective was, as well, the launch of a booklet presenting the collected stories on World Arthritis Day 2016. Methods: The ANMAR Young task force has drafted the four different writing traces to compose the campaign, investigating some crucial issues, such as: the impact of RMDs on young people's personal life, working life and education; the experience of transitioning from pediatric to adult rheumatology care services; young rheumatic patients' unmet needs and priorities. The criteria for inclusion of participants were deliberately simple: every Italian person living with any RMDs and aged from 18 to 35 could take part in the campaign. Texts have been collected anonymously exclusively through an online form, promoted and disseminated mostly through social media. The pilot project campaign has lasted one month, from the end of July 2016 until the end of August 2016. Results: From the end of July 2016 to the end of August 2016 21 stories have been submitted by 20 female respondents and 1 male respondent coming from 11 different Italian regions, suffering from different RMDs (among which the condition reported more often is Juvenile Idiopathic Arthritis). The collection has become the subject of a booklet, published in an edition of about 5, 000 copies and officially launched in October 2016 in Rome, on World Arthritis Day. The campaign spread online, allowing ANMAR Young to gather different experiences, expand its network, contribute in the process of empowerment and engagement of Italian young rheumatic patients. Conclusions: The campaign Keep Calm and Tell Me Your Story! has proved to be a valuable, peer-to-peer, economically sustainable, easily manageable and repeatable (also abroad) engaging tool for raising awareness about the impact of RMDs on the quality of life of young people. We intend to further develop this narrative medicine experience by keeping collecting new stories, by sharing them weekly through social media, by promoting our printed booklet. We intend to further analyze in detail the collected texts, in order to read them not only as personal experiences but also as a qualitative mapping of Italian young people with RMDs' unmet needs and priorities. Disclosure of Interest: None declared